(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Community outreach efforts are crucial in addressing visual health disparities and promoting eye care awareness, particularly in underserved communities. Optic technician-nurse teams are uniquely positioned to lead impactful initiatives beyond clinic settings. This abstract explores the innovative approaches employed by these teams in engaging communities to enhance eye health and well-being. By understanding community needs, designing tailored programs, and overcoming logistical challenges, optic technician-nurse teams deliver education, screenings, and resources to those in need. Success stories demonstrate the tangible impact of these initiatives on individual lives and community health outcomes. Looking ahead, opportunities for scaling up outreach efforts through technology and advocacy are highlighted. This abstract underscores the importance of collaborative, community-centered approaches in ensuring equitable access to eye care.